1993
DOI: 10.1128/jcm.31.2.422-425.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of seven respiratory viruses in shell vials: a practical and highly sensitive method

Abstract: The isolation of respiratory viruses in shell vials was compared with isolation in tube cultures in order to determine the sensitivity of the former, rapid method. Twenty of 21 influenza virus and 15 of 15 parainfluenza virus isolates were recovered in shell vials. One hundred twenty-seven of 138 respiratory syncytial virus isolates were detected in shell vials, but only 10 of 21 adenovirus isolates were positive by the rapid method. Shell vials are very effective for the diagnosis of respiratory viral infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 17 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…By changing the cell line grown on the coverslip and the specificity of the MAbs used for staining, detection of other viruses was easily facilitated. HSV (63), influenza virus (45,130), mumps virus (56), various respiratory viruses (108,117,126), enteroviruses (155), adenoviruses (155), dengue virus (136), and VZV (15,161) have been isolated in shell vials. Recent studies by Landry et al (85) demonstrated the ability to detect hMPV by day 2 postinoculation in A549, HEp-2, and LLC-MK2 shell vials when stained with a MAb (MAb 8510; Chemicon International, Temecula, CA) to hMPV matrix protein.…”
Section: Centrifugation-enhanced Inoculation and Pre-cpe Detection Ofmentioning
confidence: 99%
“…By changing the cell line grown on the coverslip and the specificity of the MAbs used for staining, detection of other viruses was easily facilitated. HSV (63), influenza virus (45,130), mumps virus (56), various respiratory viruses (108,117,126), enteroviruses (155), adenoviruses (155), dengue virus (136), and VZV (15,161) have been isolated in shell vials. Recent studies by Landry et al (85) demonstrated the ability to detect hMPV by day 2 postinoculation in A549, HEp-2, and LLC-MK2 shell vials when stained with a MAb (MAb 8510; Chemicon International, Temecula, CA) to hMPV matrix protein.…”
Section: Centrifugation-enhanced Inoculation and Pre-cpe Detection Ofmentioning
confidence: 99%
“…The test with the enterovirusspecific MAb scored negative for echovirus types 22, 23, and 25 and some strains of echovirus 1 and 3. Fifteen clinical adenovirus isolates that belonged to types 1,2,3,4,5,7,8,9,10,11,15,17,19,20, and 21 and that had been stored at Ϫ70°C were examined and tested positive by both techniques (data not shown).…”
Section: Influence Of Cell Type On the Rates Of Detection Of Enterovimentioning
confidence: 99%
“…Of the more recently developed methods, the use of nucleic acid amplification techniques for the direct detection of enteroviruses and adenoviruses in clinical specimens is available only in laboratories highly specialized for the diagnosis of viral infections (7). On the other hand, rapid techniques with short-term culture and immunofluorescence for the detection of, for example, respiratory viruses in clinical specimens are widely used (2,6,11,12,15). Application of this approach for the examination of fecal specimens for adenoviruses and enteroviruses has been reported less often (17,19,20).…”
mentioning
confidence: 99%
“…All adenovirus isolates were inoculated in duplicate into human lung carcinoma (A549) cell tube cultures obtained from BioWhittaker Inc. (Walkersville, MD) and ViroMed Laboratories, Inc. (Minnetonka, MN). The use of conventional tube cultures for the isolation of adenoviruses in the clinical setting remains our system of choice, specifically with consideration to those specimens containing low viral titers [21]. All isolates were passaged at least once into tube cultures of the same cell type.…”
Section: Cell Cultures and Specimen Inoculationmentioning
confidence: 99%
“…Utilizing the human lung carcinoma (A549) cell culture as our indicator system, two viral induced monolayer degenerations (i.e., cytopathic effects or CPEs) were recognized. Among our wild and the laboratory adapted (i.e., ATCC) adenovirus isolates tested in this study, serotypes 1,2,4,5,6,8,11,19,21, 27, and 31 were expectedly characterized by the typically enlarged, rounded, and refractile cells, which eventually aggregated into irregular 'grape-like' clusters. Adenovirus types 3 and 7, however, were characterized by the development of distinct intranuclear inclusions, a flattening and then a web or net-like monolayer degeneration.…”
mentioning
confidence: 99%